Assessment of Lead and Cadmium Mobility in Calcareous Soil Under the Impact of Farmyard Manure (FYM) and Wastewater Irrigation - Fatihi, Manal Zaki; Hassan, Khalida (Sulaimani Journal for Pure and Applied Sciences, 2025)
The leachability as well as the distribution of cadmium (Cd) and lead (Pb) were studied in two different calcareous soils treated with sheep manure (FYM) and wastewater (WW). The FYM thoroughly mixed with surface soils at three levels (F0, F20, and F40 g kg⁻¹), and the treated soils were incubated for 45 days. Soil columns were subjected to the intermittent leaching for ten times (seven days’ intervals) using waste water, and the leachates were collected for analysis of pH, EC, Pb, Cd, anions, and cations. The soils in the columns were divided into two depths (0-12 cm and 12-24 cm) and then analyzed. Results showed that EC, Na⁺, Cl⁻, K⁺ and SO₄⁻² of incubated soils increased due to manure application. Pb was higher in the soil treated with 20 g kg⁻¹, while Cd levels were very low (0.0095–0.0170 mg kg⁻¹). Wastewater application lowered the leachate pH of both soils and sharply increased EC. Cd concentrations slightly decreased, while Pb of the leachates across all treatments remained between (0.0218–0.0274 mg kg⁻¹. Comparing the two depths of the soil, Pb concentrations were consistently lower in the 12–24 cm layer compared to 0–12 cm, indicating Pb retention in surface soil, with limited downward mobility. However, Cd concentrations increased in the 12–24 cm layer under wastewater irrigation, especially at F20 WW (0.0121 mg kg⁻¹) and F40 WW (0.0141 mg kg⁻¹). This confirms the vertical movement of soluble Cd and the potential environmental risks of Cd migration under combined wastewater and organic amendments in calcareous soils.
Keywords: Manure; Lead; Cadmium; Mobility; Calcareous soil; Wastewater